SURROGATE MOTHERHOOD – ABUSE OF FINANCIAL (IN)ABILITY OR SOCIALLY ACCEPTABLE FAMILY PLANNING METHOD - Jančić Mihić, Melanija (Serbian political thought, 2025)
Surrogate motherhood, as one of the most sensitive and controversial issues not only in the field of contemporary family law, but also in the field of human rights law in general, has its foundations both in medical advancements and achievements and in the evolution of legal and societal awareness. Surrogacy, as an important family-building pathway, is primarily driven by a profound desire of intended parents for parenthood and the fulfillment of the most important role in life. In this paper, the author will analyze surrogate motherhood, especially focusing on the proposed legal framework of altruistic-gestational surrogacy within the Pre-draft of the Civil Code of Serbia. Using normative and axiological methods, it is questionable whether and which type of surrogacy should be understood as an abuse of rights and medical achievements. Having in mind numerous advantages of precise and restrictive provisions of surrogate motherhood as proposed in the Pre-draft of the Civil Code, it would be preferable to consider surrogacy, established as a method of female infertility treatment, a socially acceptable method of family planning.
Keywords: surrogate motherhood; family planning; female infertility treatment; surrogation; biomedically assisted reproduction; intended parenthood; assisted parenthood; third-party reproduction